PENGEMBANGAN BAHAN AJAR HIMPUNAN DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA KELAS VII SEKOLAH MENENGAH PERTAMA - Simanullang, Jonny; Darmawijoyo; Somakim (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2013)
This research is a research development that aims to produce valid teaching materials, practical and effective for learning mathematics in class VII SMP Negeri 4 Pangkal Pinang. The subjects of this study are students of class VII.D as many as 36 students. With the conclusion that the teaching materials developed in this study are categorized as valid, practical and have potential effect on student learning outcomes in class VII.D SMP Negeri 4 Pangkal Pinang. DOI: https://doi.org/10.22342/jpm.7.1.4644.